Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có : \(M=-\dfrac{7}{10^{2011}}+\dfrac{-15}{10^{2012}}\) và \(N=\dfrac{-15}{10^{2011}}+\dfrac{-8}{10^{2012}}\)
Xét \(M=-\dfrac{7}{10^{2011}}-\dfrac{15}{10^{2012}}=-\dfrac{1}{10^{2011}}\left(7+\dfrac{15}{10}\right)=-\dfrac{1}{10^{2011}}\cdot\dfrac{17}{2}\).
Xét \(N=-\dfrac{15}{10^{2011}}-\dfrac{8}{10^{2012}}=-\dfrac{1}{10^{2011}}\left(15+\dfrac{8}{10}\right)=-\dfrac{1}{10^{2011}}\cdot\dfrac{79}{5}\).
Ta cũng có : \(\dfrac{M}{N}=\dfrac{-\dfrac{1}{10^{2011}}\cdot\dfrac{17}{2}}{-\dfrac{1}{10^{2011}}\cdot\dfrac{79}{5}}=\dfrac{\dfrac{17}{2}}{\dfrac{79}{5}}=\dfrac{85}{158}\)
\(\Rightarrow M=\dfrac{85}{158}N\). Mà \(\dfrac{85}{158}< 1\) nên \(M< N\).
Vậy : \(M< N\).
Cho C=\(10^{2010}+\frac{1}{10^{2010}}\)
Xét \(A_1=10^{2010}+\frac{1}{10^{2011}}\)và \(B^{ }_1=10^{2011}+\frac{1}{10^{2012}}\)
Ta có \(A_1-C=10^{2010}+\frac{1}{10^{2010}}-10^{2010}-\frac{1}{10^{2010}}\)
\(A_1-C=10.\left(\frac{1}{10^{2011}}-\frac{1}{10^{2010}}\right)\)
Giair tượng tự ta được \(B_1-C=10^{2010}.\left(9+\frac{1}{10^{2012}}-\frac{1}{10^{2010}}\right)\)
Ta thấy \(\frac{1}{10^{2012}}-\frac{1}{10^{2010}}<\frac{1}{10^{2011}}-\frac{1}{2010}\)\(\Leftrightarrow\frac{1}{10^{2012}}<\frac{1}{10^{2011}}\Rightarrow9+\frac{1}{10^{2012}}>\frac{1}{10^{2011}}\)
=> A1-C<B1-C=>A1<B1=> A1+1<B1+1 HAY A<B
\(xet:M-N=-\frac{7}{2^{2011}}+\frac{-15}{10^{2012}}-\left(-\frac{15}{10^{2011}}+\frac{-8}{10^{2012}}\right)=\frac{8}{2^{2011}}-\frac{7}{2^{2012}}\)
\(=\frac{1}{2^{2011}}\left(8-\frac{7}{2}\right)>0\)
Vậy M>N